Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7510890
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic strict fractional frequency reuse for software-defined 5G networks

Abstract: The surge of mobile data traffic has spurred academia and industries to begin developing 5G networks. 5G is meant to overcome limitations of 4G cellular technology relying on the dominant trend of mobile network densification with the deployment of small cell base stations. To accelerate this process, low complexity and inexpensive remote radio heads (RRHs) are deployed massively and connected to a centralized pool of resources. In this work, we study the problem of inter-cell interference (ICI) which arises i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It simply adds a factor in terms of variance (cf. (20)). We simulate the different strategies through a simulator coded in C available here (http://www.anthonybusson.fr/index.php/publications).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It simply adds a factor in terms of variance (cf. (20)). We simulate the different strategies through a simulator coded in C available here (http://www.anthonybusson.fr/index.php/publications).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In all simulations and numerical results we consider 50 eNodeB. The different sums in the equations (e.g., (10) and (20)) are then limited to 50. For each set of parameters, simulations have be run from 10,000 to several millions times depending on the evaluated quantities.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouras et al provide a techno‐economic analysis for the introduction of softwarization technologies in the 5G network architecture, with a cost model to estimate the CAPEX and OPEX of the proposed architecture. Gebremariam et al proposed two scheduling solutions to manage the remote radio heads (RRHs) unit and control intercell interference. They assumed that small cell coverage area can be dynamically divided in different numbers of sectors to take into account traffic loads and interference suffered from interior and cell edge users.…”
Section: Related Workmentioning
confidence: 99%
“…Super and regular subcarrier groups serve both center and edge users in the entire area and the sector. In [15], the authors suggested that the dynamic strict FFR would depend on the spatial scheduling of channels that would eliminate interference. The cell is dynamically divided into sectors, unlike the strict static FFR, which divides it into three static sectors.…”
Section: Introductionmentioning
confidence: 99%